2021
DOI: 10.3390/cells10123597
|View full text |Cite
|
Sign up to set email alerts
|

7-Ketocholesterol Induces Lipid Metabolic Reprogramming and Enhances Cholesterol Ester Accumulation in Cardiac Cells

Abstract: 7-Ketocholesterol (7KCh) is a major oxidized cholesterol product abundant in lipoprotein deposits and atherosclerotic plaques. Our previous study has shown that 7KCh accumulates in erythrocytes of heart failure patients, and further investigation centered on how 7KCh may affect metabolism in cardiomyocytes. We applied metabolomics to study the metabolic changes in cardiac cell line HL-1 after treatment with 7KCh. Mevalonic acid (MVA) pathway-derived metabolites, such as farnesyl-pyrophosphate and geranylgerany… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 44 publications
(58 reference statements)
3
5
0
Order By: Relevance
“…The co-treatment with 7KCh and lovastatin reduced the HMG-CoA level by 94%. It is consistent with our previous finding that 7KCh represses the expression of Acat2 and Hmgcs1 genes [16], the products of which act upstream of HMGCR in the MVA pathway. Such a co-treatment caused a 54% decrease in the cell number (Figure 6B).…”
Section: Inhibition Of the Mevalonic Acid (Mva) Pathway Contributes T...supporting
confidence: 93%
See 4 more Smart Citations
“…The co-treatment with 7KCh and lovastatin reduced the HMG-CoA level by 94%. It is consistent with our previous finding that 7KCh represses the expression of Acat2 and Hmgcs1 genes [16], the products of which act upstream of HMGCR in the MVA pathway. Such a co-treatment caused a 54% decrease in the cell number (Figure 6B).…”
Section: Inhibition Of the Mevalonic Acid (Mva) Pathway Contributes T...supporting
confidence: 93%
“…It has been found that the basal and maximum respiration and the spare respiratory capacity are reduced in the PHB-deficient cells, with impaired organization of the respiratory supercomplexes [24,25]. Consistent with such a notion, our previous study has shown that the Phb1, Phb2, Higd1a, and Higd2a transcript levels declined in the 7KCh-treated cells [16]. Prohibin 1 (PHB1) and 2 (PHB2) participate in the assembly of respiratory supercomplexes and the maintenance of their stability [26].…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations